The dichotomy of the application of a systems approach in UK healthcare: the challenges and priorities for implementation - Pickup, Laura; Lang, Alexandra; Atkinson, Sarah; Sharples, Sarah (Taylor & Francis, 2017)
There is increasing demand for a systems approach within national healthcare guidelines to provide a systematic and sustainable framework for improvements in patient safety. Supported by this is the growing body of evidence within Human Factors/Ergonomics (HFE) healthcare literature for the inclusion of this approach in health service design, provision and evaluation. This paper considers the current interpretation of this within UK healthcare systems and the dichotomy which exists in the challenge to implement a systems approach. Three case studies, from primary and secondary care, present a systems approach, offering a novel perspective of primary care and blood sampling. These provide practical illustrations of how HFE methods have been used in collaboration with healthcare staff to understand the system for the purpose of professional education, design and safety of clinical activities. The paper concludes with the challenge for implementation and proposes five roles for systems HFE to support patient safety.